The use of graphic representation at the lessons of natural science - Bernotas , V. (Psichologija, 1971)
Graphic representation plays an important part in the process of training. It helps not only to extend pupils’ knowledge but also to systematize and classify it, to reveal causality between things and phenomena; it develops logical thinking and habits of independent work. The article reveals possibilities of using graphic representation (tables, diagrams, schemes, graphs) at the lessons of natural science and geography in the 4th and 5th classes, analyses the material of weather observations and estimates the effectiveness of graphic representation.